Lipomatous Cystic Meningioma Mimicking High Grade Glioma: A Rare Case Report with Brief Review of Literature - Karki, Mohan; Roka, Yam (Nepal Journal of Neuroscience, 2022)
Lipomatous meningioma is rare variant of meningioma. A 34 year old male was presented with intermittent headache, dizziness, slurring of speech and right hand numbness and weakness since 15days. Patient came at OPD with Computed Tomography (CT) scan and it reported that a well defined thick walled heterogeneous mass. Brain magnetic resonance imaging (MRI) was done where it reported that large (6.3 x 6.5 x 4.7 cm) T1 hypo-intense and T2 hyer-intesne enhancing mass with non-enhancing cystic lesion and surrounding edema in left parietal lobe suggesting high grade glioma. Left parietal craniotomy and total excision of mass was performed. Histopathology diagnosis was a rare Lipomatous Meningioma.